Physical examinations and whole-body imaging versus physical examinations alone during follow-up after radical surgery of stage IIB–C and III cutaneous malignant melanoma (TRIM) : an interim analysis of a multicentre, randomised, phase 3 trial in Sweden - Ladjevardi, Cecilia O.; Naeser, Ylva; Dyrke, Ulf; Papantoniou, Dimitrios; Bagge, Roger Olofsson; Elander, Nils; Ingvar, Christian; Flygare, Petra; Nilsson, Cecilia; Jakobsson, Frida; Lange-Norström, Katrin; Sundin, Anders; et al. (The Lancet Oncology, 2025)
Background In several countries, whole-body imaging has been introduced in the routine follow-up of individuals with high-risk cutaneous malignant melanoma after surgery. However, there is scarce evidence that earlier detection of recurrent disease by regular scanning improves survival. In this interim analysis, we investigated whether imaging in the follow-up programme for high-risk cutaneous malignant melanoma improves survival and assessed whether the study should continue to include participants. Methods TRIM is a multicentre, randomised, phase 3 trial in Sweden. Eligible participants are aged 18 years and older with sufficient renal function for intravenously contrast-enhanced CT and are expected to be fit for treatment in case of recurrence. After radical surgery of stage IIB–C and III cutaneous malignant melanoma, participants were randomly assigned (1:1, stratified by tumour stage and method of radiological assessment) to 3 years of follow-up by physical examinations alone (standard group) or to physical examinations plus whole-body imaging with CT or [18F]fluorodeoxyglucose-PET-CT at baseline, 6, 12, 24, and 36 months (experimental group). The goal is to include 1300 participants. The primary endpoint is overall survival at 5 years and will be reported in the final analysis when data are mature. In this interim report, no endpoints were predefined; we present overall survival, relapse-free survival, locoregional relapse-free survival, and distant metastasis-free survival, analysed by intention to intervene. This study is registered with ClinicalTrials.gov , NCT03116412 , and recruitment is ongoing. Findings Between June 8, 2017, and July 28, 2023, 983 participants were randomly allocated to the standard (n=498; 296 [59%] male, 202 [41%] female) or experimental (n=485; 309 [64%] male, 176 [36%] female) group. There were no statistically significant differences in overall survival (not reached [NR; 95% CI NR–NR] vs NR [NR–NR]; hazard ratio [HR] 1·04 [95% CI 0·71–1·51], p=0·85) or distant metastasis-free survival (NR [NR–NR] vs NR [NR–NR]; HR 1·20 [0·89–1·64], p=0·24) between the groups at a median follow-up time of 33·6 months (IQR 16·3–49·8). 3-year overall survival rates were 88·2% (95% CI 85·0–91·6) in the standard group versus 87·7% (84·3–91·3) in the experimental group and distant metastasis-free survival was 81·6% (77·9–85·6) in the standard group versus 79·3% (75·3–83·5) in the control group. Interpretation This interim analysis indicated that there is no benefit from imaging in the follow-up programme for individuals with high-risk cutaneous malignant melanoma. However, only a few participants have completed the follow-up time of 5 years, and the numerical difference between the study groups in distant metastasis-free survival motivates us to continue the study according to protocol. Funding Stiftelsen Onkologiska Klinikens i Uppsala Forskningsfond and Uppsala University Hospital.
Publisher Copyright: © 2025 Elsevier Ltd.